Ferroptosis-Related Transcriptional Level Changes and the Role of CIRBP in Glioblastoma Cells Ferroptosis - Zijiang Yang; Ting Zhang; Xuanlin Zhu; Xiaobiao Zhang (Biomedicines)
Background/Objective: We aimed to elucidate the roles of ferroptosis-associated differentially expressed genes (DEGs) in glioblastoma and provide a comprehensive resource for researchers in the field of glioblastoma cell ferroptosis. Methods: We used RNA sequencing to identify the DEGs associated with erastin-induced ferroptosis in glioblastoma cells. We further unraveled the biological functions and clinical implications of cold-inducible RNA-binding protein (CIRBP) in the context of glioblastoma by using a multifaceted approach, encompassing gene expression profiling, survival analysis, and functional assays to elucidate its role in glioblastoma cell mortality and its potential influence on patient prognosis. Results: We identified and validated the gene encoding CIRBP, the expression of which is altered during glioblastoma ferroptosis. Our findings highlight the relationship between CIRBP expression and ferroptosis in glioblastoma cells. We demonstrated that CIRBP modulates key aspects of cell death, thereby altering the sensitivity of glioblastoma cells to erastin-induced ferroptosis. A prognostic model, constructed based on CIRBP expression levels, revealed an association between lower CIRBP levels and poorer prognosis in glioma patients; this finding was corroborated by our comprehensive in vitro and in vivo assays that highlighted the impact of modulating CIRBP expression on glioblastoma cell viability and ferroptotic response. Conclusion: Our research unravels the complex molecular dynamics of ferroptosis in glioblastoma and underscores CIRBP as a potential biomarker and therapeutic target. This improved understanding of the role of CIRBP in ferroptosis paves the way for more precise and efficacious treatments for glioblastoma, potentially improving patient outcomes.